Adsorption based downstream processing approach for penicillin V from a Penicillium chrysogenum BIONCL I22 culture filtrate - Mishal, Bela H.; Das, Sancharini; Mahajan, Vaishnavi N.; Dharne, Mahesh S.; Joshi, Rakesh S.; Giri, Ashok P. (ACS Omega, 2024)
Penicillin V (phenoxy methyl penicillin) is highly sought after among natural penicillins because of its exceptional acid stability and effectiveness against common skin and respiratory infections. Given its wide-ranging therapeutic uses, there is a need to establish a greener method for its maximum recovery to reduce the carbon footprint. Here, we have identified and validated optimized operational conditions for resin-based penicillin V recovery. It was observed that Amberlite XAD4 had the highest penicillin V hydrophobic adsorption capacity among the other screened resins. Kinetic and isothermal studies using linear and nonlinear regression analysis showed that the adsorption process well fitted with pseudo-second-order kinetics (R-2 = 0.9816) and the Freundlich adsorption isotherm model (R-2 = 0.9871). Adsorption equilibrium was attained within 4 h, while maximum adsorption was observed at 3 mg/mL penicillin V concentration. Furthermore, the optimized extraction protocol was compared with the conventional butyl acetate-based downstream processing. Under optimum conditions resin-based penicillin V recovery was 2-fold higher as compared to the solvent extraction method and the resin could be reused for over six cycles without compromising the yield. These findings signify substantial progress toward the development of an environmentally sustainable approach for penicillin V recovery and a potentially viable method for extractive fermentation.

Discovery of free glycated amines and glycated urea in diabetic plasma: potential implications in diabetes - Shaikh, Rashdajabeen Q.; Das, Sancharini; Chaurasiya, Arvindkumar; Ashtamy, Murali G.; Sheikh, Amreen B.; Fernandes, Moneesha; Tiwari, Shalbha; Unnikrishnan, Ambika G.; Kulkarni, Mahesh J. (ACS Omega, 2024)
The role of protein glycation in the pathogenesis of diabetes has been well established. Akin to proteins, free amino acids and other small-molecule amines are also susceptible to glycation in hyperglycemic conditions and may have a role in the pathogenesis of the disease. However, information about glycation of free amino acids and other small-molecule amines is relatively obscure. In the quest to discover small-molecule glycated amines in the plasma, we have synthesized glycated amino acids, glycated creatine, and glycated urea, and by using a high-resolution accurate mass spectrometer, a mass spectral library was developed comprising the precursor and predominant fragment masses of glycated amines. Using this information, we report the discovery of the glycation of free lysine, arginine, and leucine/isoleucine from the plasma of diabetic patients. This has great physiological significance as glycation of these amino acids may create their deficiency and affect vital physiological processes such as protein synthesis, cell signaling, and insulin secretion. Also, these glycated amino acids could serve as potential markers of diabetes and its complications. While other amines, such as creatinine and urea, accumulate in the plasma and act as biomarkers of diabetic nephropathy. For the first time, we report the detection of glycated urea in diabetic plasma, which is confirmed by matching the precursor and fragment masses with the in vitro synthesized glycated urea by using C-12(6) and C-13(6)-glucose. Further, we quantified glycated urea detected in two forms, monoglycated urea (MGU) and diglycated urea (DGU), by a targeted mass spectrometric approach in the plasma of healthy, diabetic, and diabetic nephropathy subjects. Both MGU and DGU showed a positive correlation with clinical parameters, such as blood glucose and HbA1c. Given that urea gets converted to glycated urea in hyperglycemic conditions, it is crucial to quantify MGU and DGU along with the urea for the diagnosis of diabetic nephropathy and study their physiological role in diabetes.

Microbial production of N-acetyl-D-glucosamine (GlcNAc) for versatile applications: biotechnological strategies for green process development - Das, Sancharini; Chowdhury, Chiranjit; Kumar, S. Pavan; Roy, Debasis; Gosavi, Suresh W.; Sen, Ramkrishna (Carbohydrate Research, 2024)
N-acetyl-D-glucosamine (GlcNAc) is a commercially important amino sugar for its wide range of applications in pharmaceutical, food, cosmetics and biofuel industries. In nature, GlcNAc is polymerised into chitin biopolymer, which is one of the major constituents of fungal cell wall and outer shells of crustaceans. Sea food processing industries generate a large volume of chitin as biopolymeric waste. Because of its high abundance, chitinaceous shellfish wastes have been exploited as one of the major precursor substrates of GlcNAc production, both in chemical and enzymatic means. Nevertheless, the current process of GlcNAc extraction from shellfish wastes generates poor turnover and attracts environmental hazards. Moreover, GlcNAc isolated from shellfish could not be prescribed to certain groups of people because of the allergic nature of shell components. Therefore, an alternative route of GlcNAc production is advocated. With the advancement of metabolic construction and synthetic biology, microbial synthesis of GlcNAc is gaining much attention nowadays. Several new and cuttingedge technologies like substrate co-utilization strategy, promoter engineering, and CRISPR interference system were proposed in this fascinating area. The study would put forward the potential application of microbial engineering in the production of important pharmaceuticals. Very recently, autotrophic fermentation of GlcNAc synthesis has been proposed. The metabolic engineering approaches would offer great promise to mitigate the issues of low yield and high production cost, which are major challenges in microbial bio-processes industries. Further process optimization, optimising metabolic flux, and efficient recovery of GlcNAc from culture broth, should be investigated in order to achieve a high product titer. The current study presents a comprehensive review on microbe-based eco-friendly green methods that would pave the way towards the development of future research directions in this field for the designing of a cost-effective fermentation process on an industrial setup.
Keywords: Genetic engineering; GlcNAc applications; Market status; Microbial bioprocess; N-acetyl-D-glucosamine; synthetic biology